The effect of return on assets,return on equity and earnings per share on the price of banking companies listed on the Indonesian stock exchange - Rayhan Sena, Mufadhal; Adji Prabawa, Sri (Institute of Computer Science (IOCS), 2023)
This study aims to determine and provide empirical evidence that return on assets, return on equity, and earnings per share have a significant effect on stock prices in banking companies listed on the Indonesian stock exchange for the period 2018-2022. the data used are in the form of annual financial reports of banking companies that are sampled in the study with an annual period. the sample of this study was determined using purposive sampling method so that 44 companies were obtained. the type of data used is secondary data. the analysis method used is multiple linear regression, namely the classical assumption test, and hypothesis testing. the results showed that partially the variable return on assets has no effect on stock prices. the variable return on equity affects stock prices. and the earnings per share variable affects stock prices. simultaneously return on assets, return on equity, and earnings per share all affect stock prices together or simultaneously.